College students’ knowledge, attitudes, and practices of garbage sorting and their associations: a cross-sectional study of several universities in Beijing, China - Liu, Siyuan; Liu, Xiong; Li, Yibo; Yang, Dongli; Li, Feng; Yang, Junling (Frontiers in Public Health, 2024)
Background: In recent years, the Chinese government has increasingly prioritized environmental development. Effective waste separation in schools is crucial for establishing an ecological civilization in China. OBJECTIVE: The purpose of this study was to assess the knowledge, attitude, and practice of waste separation among Chinese university students, as well as to understand the demographic factors influencing the KAP of the interviewed students. These socio-demographic factors include gender, age, education, and family environment. METHODS: Based on the Knowledge ， Attitude ， Practice (KAP) theoretical model and the Lewin Behavioral Model (LBM), this study developed its questionnaire on college students' KAP of rubbish sorting. A survey was conducted on 1,282 college students from five colleges and universities in Beijing. One-way ANOVA, Pearson's correlation analysis, and multiple linear stepwise regression were employed to explore the factors influencing college students' KAP scores on waste sorting. The questionnaire's reliability and validity were effectively verified through two rounds of Delphi expert consultation. RESULTS: The scores for KAP dimensions were 55.64%, 69.18%, and 54.8%, respectively. The overall KAP score of university students on waste classification was 46.93±9.93, with a percentage score of 62.57%. More than half of college students lack clear knowledge about waste classification. Grade, gender, major, highest family education, and family economic status all impact college students' KAP scores on waste classification. There is a certain deficiency in school education on waste classification, with only 30.7% reporting having received such education. CONCLUSION: This study reveals the overall KAP score of waste separation among Chinese college students, which is marginally acceptable. Interviewed students demonstrate a positive attitude and willingness to engage in waste separation, yet improvements are needed in knowledge and practices. Lack of knowledge about waste sorting emerges as the primary influence on individuallevel practices. Consideration should be given to enhancing education and management of waste separation among college students, emphasizing the cultivation of an eco-conscious culture, and guiding students to establish correct ecological values.